Review Theories of Subjective Well-being and the Impact of Stress: The Mediating Effect of Resilience - LIU, XIAOHONG; Fernando, Yudi (International Journal of Innovation Research in Education, Technology and Management, 2024)
The study aims to investigate the impact of related stress on Chinese university students’ Subjective well-being in the context of the mediating effect of resilience. Related theories were studied and analysed and therein significant contributions leading to the understanding of the relationship between the variables were inferred. Thus, academic, employment, interpersonal and financial stresses proved to be important ingredients in shaping the subjective well-being of Chinese student. Coping techniques such as resilience was proposed, and the technique was extensively analysed to determine the degree of the contribution it will offer in mitigating stress by the Chinese university students. Theories such as social comparison theory, telic theory, personalitytheory, coping theory and stress response theory were consulted in understanding the study contributions. The study suggested further research on strategies that can be adopted in mitigating stress affecting the Chinese university students.